2020
DOI: 10.3390/nu12113292
|View full text |Cite
|
Sign up to set email alerts
|

Negative Affectivity and Emotion Dysregulation as Mediators between ADHD and Disordered Eating: A Systematic Review

Abstract: Attention-Deficit/Hyperactivity Disorder (ADHD) is associated with disordered eating, especially addictive-like eating behavior (i.e., binge eating, food addiction, loss of control overeating). The exact mechanisms underlying this association are unclear. ADHD and addictive-like eating behavior are both associated with negative affectivity and emotion dysregulation, which we hypothesized are mediators of this relationship. The purpose of this systematic review was to review the evidence related to this hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 142 publications
1
27
0
Order By: Relevance
“…These results are consistent with prior studies conducted by Alfonsson et al (2013) and Nielsen et al (2017) with the same population, with estimated ADHD prevalence of 8.3 and 8.6% respectively. Most of the literature reports that disordered eating involving binging/purging behavior is associated with a higher prevalence of ADHD symptomatology, varying between 12 and 37.1% (El Archi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with prior studies conducted by Alfonsson et al (2013) and Nielsen et al (2017) with the same population, with estimated ADHD prevalence of 8.3 and 8.6% respectively. Most of the literature reports that disordered eating involving binging/purging behavior is associated with a higher prevalence of ADHD symptomatology, varying between 12 and 37.1% (El Archi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Initial support to this hypothesis has been provided in a study reporting that emotion dysregulation may mediate the effects of negative affectivity on BE (Kukk and Akkermann, 2020). Further support comes from a previous review that suggested a mediational role of emotion dysregulation and negative affectivity in the ADHDaddictive-like eating relationship (El Archi et al, 2020), and from a previous study highlighting the mediational role of mood and feelings in the association between inattention symptoms of ADHD and risk of disordered eating (Martin et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…These seven original studies investigate the factors associated with this phenotype in different contexts: patients seeking treatment for an eating disorder, including anorexia nervosa, bulimia nervosa or binge eating disorder [ 12 , 13 ], patients seeking treatment for obesity (i.e., bariatric surgery candidates) [ 14 ], and non-clinical populations (i.e., persons not directly seeking treatment for these conditions) such as adolescents [ 15 ], female restrained eaters [ 16 ], and persons with weight-related disorders recruited in the general population [ 17 ]. This special issue also present four literature reviews that focus on: neuroimaging of sex/gender differences in obesity, in which FA is prevalent [ 18 ], involvement of the melanocortin system in binge eating, food reward and motivation [ 19 ], association between addictive-like eating behavior and attention-deficit/hyperactivity disorder (ADHD) [ 20 ], and a discussion about the FA concept and its practical implications through four complementary disciplines: addiction medicine, nutrition, health psychology, and behavioral neuroscience [ 21 ].…”
mentioning
confidence: 99%
“…For example, added sugar in a person's diet has been associated with impulsive choices (9), and vitamin deficiencies of E, C, and B12 have been associated with obsessive-compulsive disorder (10). Poor diet (e.g., sugarsweetened beverages, processed foods) coupled with loss of control over eating (e.g., over-eating) have been linked, to a variety of impulsive/compulsive symptoms, such as attentiondeficit hyperactivity disorder (ADHD) and (relatedly) bingeeating (11)(12)(13). BFRBs have impulsive/compulsive features, such as impaired response inhibition and ritualized behaviors, and comorbidities such as obsessive-compulsive disorder and behavioral addictions (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%